2019
DOI: 10.1115/1.4042426
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Solution Space in Engineering Design Education: A Simulation-Based Investigation of Product Dissection

Abstract: Product dissection has been highlighted as an effective means of interacting with example products in order to produce creative outcomes. While product dissection is often conducted as a team in engineering design education, the research on the effectiveness of product dissection activities has been primarily limited to individuals. Thus, the purpose of this study was to investigate the impact of the type(s) of product dissected in a team environment on encouraging creative design outcomes (variety, novelty, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…A literature search revealed different methods by which researchers have envisaged a design support tool for designers. These include computational support that works like recommender system (Verhaegen et al, 2011), tools to support the exploration of problem space (Murray et al, 2019), solution space (Alzayed et al, 2019), idea generation strategies (Studer et al, 2018) and framework for engineering design instruction (Crismond & Adams, 2012).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature search revealed different methods by which researchers have envisaged a design support tool for designers. These include computational support that works like recommender system (Verhaegen et al, 2011), tools to support the exploration of problem space (Murray et al, 2019), solution space (Alzayed et al, 2019), idea generation strategies (Studer et al, 2018) and framework for engineering design instruction (Crismond & Adams, 2012).…”
Section: Related Workmentioning
confidence: 99%
“…Fostering students' ability to expand the problem and solution space can help them find design solutions that are more effective, mature, and of higher quality (Alzayed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As new design issues are created and introduced, the design space changes through expansion. Design space expansion has been linked to creativity (Dorst and Cross, 2001): researchers argued that a larger design space creates more opportunities for generating novel, useful and surprising, i.e., creative designs (Alsager Alzayed et al, 2019;Gero and Kan, 2016). Studies (e.g., Shah et al, 2000) have demonstrated that design space expansion leads to greater design variety and solutions of a higher quality and effectiveness.…”
Section: Design Space Expansionmentioning
confidence: 99%
“…Studies (e.g., Shah et al, 2000) have demonstrated that design space expansion leads to greater design variety and solutions of a higher quality and effectiveness. Therefore, it is not surprising that numerous works aimed at studying (Alsager Alzayed et al, 2019) and supporting design space expansion through the use of, for example, heuristics (Daly et al, 2012) or computational tools (Gero and Kumar, 1993;Han et al, 2018). Relatedly, several studies explored the rate at which the design space expands in a team setting (e.g., Gero and Kan, 2016;Martinec et al, 2020).…”
Section: Design Space Expansionmentioning
confidence: 99%
“…Thus, future research is warranted to determine whether empathy has a role on the type of engineering professions they select. Finally, while prior research found that the ideation patterns of first year and senior-level students differ (Alsager Alzayed et al ., 2019), this work only studied first-year students. Thus, future research is warranted to extend those findings beyond first-year students.…”
Section: Conclusion Limitations and Future Workmentioning
confidence: 99%